Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Sure, let's find the first and second derivatives of the function [tex]\( h(x) = \tan(3x + 5) \)[/tex] step by step.
### Step 1: First Derivative [tex]\( h'(x) \)[/tex]
First, recall the derivative of the tangent function:
[tex]\[ \frac{d}{dx} [\tan(u)] = \sec^2(u) \cdot \frac{du}{dx} \][/tex]
Given [tex]\( h(x) = \tan(3x + 5) \)[/tex], let's set [tex]\( u = 3x + 5 \)[/tex]. Then we need to find the derivative of [tex]\( u \)[/tex] with respect to [tex]\( x \)[/tex]:
[tex]\[ \frac{du}{dx} = \frac{d}{dx} [3x + 5] = 3 \][/tex]
Using the chain rule:
[tex]\[ h'(x) = \frac{d}{dx} [\tan(3x + 5)] = \sec^2(3x + 5) \cdot \frac{d}{dx} [3x + 5] = \sec^2(3x + 5) \cdot 3 \][/tex]
Recall the trigonometric identity:
[tex]\[ \sec^2(u) = 1 + \tan^2(u) \][/tex]
Thus, we can express the first derivative as:
[tex]\[ h'(x) = 3 \sec^2(3x + 5) = 3 (1 + \tan^2(3x + 5)) \][/tex]
Since [tex]\( h(x) = \tan(3x + 5) \)[/tex], we have:
[tex]\[ h'(x) = 3 (1 + \tan^2(3x + 5)) \][/tex]
This simplifies to:
[tex]\[ h'(x) = 3 (\tan^2(3x + 5) + 1) \][/tex]
Finally:
[tex]\[ h'(x) = 3\tan^2(3x + 5) + 3 \][/tex]
### Step 2: Second Derivative [tex]\( h''(x) \)[/tex]
Now, let's move on to the second derivative [tex]\( h''(x) \)[/tex]. Using the result from [tex]\( h'(x) \)[/tex], we get:
[tex]\[ h'(x) = 3\tan^2(3x + 5) + 3 \][/tex]
We need to differentiate [tex]\( h'(x) \)[/tex] again with respect to [tex]\( x \)[/tex]. Let's break it into two parts.
1. Differentiate [tex]\( 3\tan^2(3x + 5) \)[/tex]:
[tex]\[ \frac{d}{dx} [3\tan^2(3x + 5)] = 3 \cdot 2\tan(3x + 5) \cdot \frac{d}{dx} [\tan(3x + 5)] \][/tex]
Now, we need [tex]\( \frac{d}{dx} [\tan(3x + 5)] \)[/tex]:
[tex]\[ \frac{d}{dx} [\tan(3x + 5)] = \sec^2(3x + 5) \cdot 3 \][/tex]
Therefore:
[tex]\[ 6\tan(3x + 5) \cdot 3\sec^2(3x + 5) = 18\tan(3x + 5) \sec^2(3x + 5) \][/tex]
2. Differentiate the constant term [tex]\( 3 \)[/tex], which is [tex]\( 0 \)[/tex].
Combining these results, the second derivative is:
[tex]\[ h''(x) = 18\tan(3x + 5) \sec^2(3x + 5) \][/tex]
Recall:
[tex]\[ \sec^2(u) = 1 + \tan^2(u) \][/tex]
[tex]\[ \sec^2(3x + 5) = 1 + \tan^2(3x + 5) \][/tex]
Now substitute back:
[tex]\[ h''(x) = 18\tan(3x + 5) (1 + \tan^2(3x + 5)) \][/tex]
Simplifying:
[tex]\[ h''(x) = 18\tan(3x + 5)(1 + \tan^2(3x + 5)) = 18\tan(3x + 5) (1 + \tan^2(3x + 5)) \][/tex]
Since [tex]\( 6 \times 3 = 18 \)[/tex], we can write it as:
[tex]\[ h''(x) = 3 (6 \tan(3x + 5)^2 + 6) \tan(3x + 5) \][/tex]
However, preserving the simplified form:
[tex]\[ h''(x) = 3 (6\tan^2(3x + 5) + 6) \tan(3x + 5) \][/tex]
Hence, the final answers are:
[tex]\[ \begin{array}{l} h^{\prime}(x) = 3\tan^2(3x + 5) + 3 \\ h^{\prime \prime}(x) = 3 (6\tan^2(3x + 5) + 6) \tan(3x + 5) \end{array} \][/tex]
### Step 1: First Derivative [tex]\( h'(x) \)[/tex]
First, recall the derivative of the tangent function:
[tex]\[ \frac{d}{dx} [\tan(u)] = \sec^2(u) \cdot \frac{du}{dx} \][/tex]
Given [tex]\( h(x) = \tan(3x + 5) \)[/tex], let's set [tex]\( u = 3x + 5 \)[/tex]. Then we need to find the derivative of [tex]\( u \)[/tex] with respect to [tex]\( x \)[/tex]:
[tex]\[ \frac{du}{dx} = \frac{d}{dx} [3x + 5] = 3 \][/tex]
Using the chain rule:
[tex]\[ h'(x) = \frac{d}{dx} [\tan(3x + 5)] = \sec^2(3x + 5) \cdot \frac{d}{dx} [3x + 5] = \sec^2(3x + 5) \cdot 3 \][/tex]
Recall the trigonometric identity:
[tex]\[ \sec^2(u) = 1 + \tan^2(u) \][/tex]
Thus, we can express the first derivative as:
[tex]\[ h'(x) = 3 \sec^2(3x + 5) = 3 (1 + \tan^2(3x + 5)) \][/tex]
Since [tex]\( h(x) = \tan(3x + 5) \)[/tex], we have:
[tex]\[ h'(x) = 3 (1 + \tan^2(3x + 5)) \][/tex]
This simplifies to:
[tex]\[ h'(x) = 3 (\tan^2(3x + 5) + 1) \][/tex]
Finally:
[tex]\[ h'(x) = 3\tan^2(3x + 5) + 3 \][/tex]
### Step 2: Second Derivative [tex]\( h''(x) \)[/tex]
Now, let's move on to the second derivative [tex]\( h''(x) \)[/tex]. Using the result from [tex]\( h'(x) \)[/tex], we get:
[tex]\[ h'(x) = 3\tan^2(3x + 5) + 3 \][/tex]
We need to differentiate [tex]\( h'(x) \)[/tex] again with respect to [tex]\( x \)[/tex]. Let's break it into two parts.
1. Differentiate [tex]\( 3\tan^2(3x + 5) \)[/tex]:
[tex]\[ \frac{d}{dx} [3\tan^2(3x + 5)] = 3 \cdot 2\tan(3x + 5) \cdot \frac{d}{dx} [\tan(3x + 5)] \][/tex]
Now, we need [tex]\( \frac{d}{dx} [\tan(3x + 5)] \)[/tex]:
[tex]\[ \frac{d}{dx} [\tan(3x + 5)] = \sec^2(3x + 5) \cdot 3 \][/tex]
Therefore:
[tex]\[ 6\tan(3x + 5) \cdot 3\sec^2(3x + 5) = 18\tan(3x + 5) \sec^2(3x + 5) \][/tex]
2. Differentiate the constant term [tex]\( 3 \)[/tex], which is [tex]\( 0 \)[/tex].
Combining these results, the second derivative is:
[tex]\[ h''(x) = 18\tan(3x + 5) \sec^2(3x + 5) \][/tex]
Recall:
[tex]\[ \sec^2(u) = 1 + \tan^2(u) \][/tex]
[tex]\[ \sec^2(3x + 5) = 1 + \tan^2(3x + 5) \][/tex]
Now substitute back:
[tex]\[ h''(x) = 18\tan(3x + 5) (1 + \tan^2(3x + 5)) \][/tex]
Simplifying:
[tex]\[ h''(x) = 18\tan(3x + 5)(1 + \tan^2(3x + 5)) = 18\tan(3x + 5) (1 + \tan^2(3x + 5)) \][/tex]
Since [tex]\( 6 \times 3 = 18 \)[/tex], we can write it as:
[tex]\[ h''(x) = 3 (6 \tan(3x + 5)^2 + 6) \tan(3x + 5) \][/tex]
However, preserving the simplified form:
[tex]\[ h''(x) = 3 (6\tan^2(3x + 5) + 6) \tan(3x + 5) \][/tex]
Hence, the final answers are:
[tex]\[ \begin{array}{l} h^{\prime}(x) = 3\tan^2(3x + 5) + 3 \\ h^{\prime \prime}(x) = 3 (6\tan^2(3x + 5) + 6) \tan(3x + 5) \end{array} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.